2020
DOI: 10.1186/s12917-020-02659-y
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the intestinal microbiome of farrowing sows following the administration of garlic (Allium sativum) extract and probiotic bacteria cultures under farming conditions

Abstract: Background Due to the tendency to reduce antibiotic use in humans and animals, more attention is paid to feed additives as their replacement. Crucial role of feed additives is to improve the health status, production efficiency and performance. In this original research, we estimate the potential influence of garlic (Allium sativum) extract and probiotic formula including Enterococcus faecium, Lactobacillus rhamnosus and Lactobacillus fermentum on the intestinal microbiota of sows, using the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…In the healthy animal, a balance of micro-organisms in the gastrointestinal tract helps in efficient digestion and maximum absorption of nutrients, and increases the body's resistance to infectious diseases [38,39]. The presented study showed that BioPlus YC probiotics supplementation resulted in a higher count of B. subtilis, B. licheniformis and LAB as well as a lower count of Enterobacteriaceae, Enterococcus, Clostridium and Bacillus sp.…”
Section: Discussionmentioning
confidence: 67%
“…In the healthy animal, a balance of micro-organisms in the gastrointestinal tract helps in efficient digestion and maximum absorption of nutrients, and increases the body's resistance to infectious diseases [38,39]. The presented study showed that BioPlus YC probiotics supplementation resulted in a higher count of B. subtilis, B. licheniformis and LAB as well as a lower count of Enterobacteriaceae, Enterococcus, Clostridium and Bacillus sp.…”
Section: Discussionmentioning
confidence: 67%
“…The authors found a significant increase of Lactobacillus and a reduction in the counts of coliforms and enteropathogens (Salmonella and Clostridium) in faeces, compared to those animals that consumed a basal diet that included antibiotics but not PTSO. The analysis of microbiome in sows, reported in another recent article [78], showed the reduction of intestinal pathogenic species in those animals that ingested an extract composed of garlic and probiotics, compared to the control group. Moreover, in another assay conducted in swine [65], another extract containing PTS and PTSO was used as a feed additive.…”
Section: Discussionmentioning
confidence: 95%
“…Two extra articles not identified by the electronic databases were added as the authors were aware of their existence. Finally, as shown in Figure 3, a total of 17 articles [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] were found to be eligible for the present systematic review following the full-text eligibility assessment. The characteristics of the selected articles are summarized in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations